Piglets productivity for dry, wet and liquid type of feeding on growing - Вдовіченко, Ю. В.; Нечмілов, В. М.; Повод, М. Г. (Scientific Progress & Innovations, 2018)
A comparative study of the productivity of hybrid pigs of Irish company Hermitage Genetics was carried out in identical conditions of maintenance on growing in dry (self-feeder), wet (with moistening in feeders) and liquid (multiphase) feeding types. Piglets that were grown for a liquid multiphase type of feeding consumed more than 12.4 % of the daily food each day had higher average daily gains of 7.0 and 18.3 %, with absolute increases of 7.3 and 18.4 %. At the end of growing, animals fed on a liquid type of feeding had 5.6 and 13.9 % higher live weight, compared to animals that consumed wet during the growing, with moisturizing in feeders and dry feed, respectively. At the same time, they gave way to animals that received a wet and dry type of feeding on growing, with preservation number of pigs by 1.6 and 1.3 %, and had worse feed conversion by 9.2 and 1.6 %, respectively. Piglets for wet (with moisture in the feeders) type of feeding consumed 9.2 % less feed and, as a result, had on growing period lower by 7.0 % average daily, 7.3 % absolute, 2.8 % relative growth and 5.6 % lower live weight at the end of growing, but 9.2 % better feed conversion and 1.6 % survivability compared to analogues, were keeping for liquid multiphase type of feeding. While they dominated analogues that consumed on growing dry food, with an average daily 10.6 %, absolute 10.3 % and relative gains by 5.0 %, preservation by 0.3 %, feed conversion by 7.5 % and reached at the end of growing period by 7.8 % more live weight.